Docetaxel (DTX)-loaded polydopamine-modified TPGS-PLA nanoparticles as a targeted drug delivery system for the treatment of liver cancer. (15th January 2016) - Zhu, Dunwan; Tao, Wei; Zhang, Hongling; Liu, Gan; Wang, Teng; Zhang, Linhua; Zeng, Xiaowei; Mei, Lin
Graphical abstract: In vivo imaging and biodistribution analysis of nude mice bearing HepG2 tumors after tail vein injection of free IR-780, or IR-780 loaded TPGS-PLA/NPs or Gal-pD-TPGS-PLA/NPs. The results suggest that Gal-pD-TPGS-PLA/NPs prepared in the study specifically interacted with the hepatocellular carcinoma cells through ligand–receptor recognition and could therefore potentially be used as a drug delivery system targeting liver cancers. Abstract: Polydopamine-based surface modification is a simple way to functionalize polymeric nanoparticle (NP) surfaces with ligands and/or additional polymeric layers. In this work, we developed DTX-loaded formulations using polydopamine-modified NPs synthesized using D-α-tocopherol polyethylene glycol 1000 succinate-poly(lactide) (pD-TPGS-PLA/NPs). To target liver cancer cells, galactosamine was conjugated on the prepared NPs (Gal-pD-TPGS-PLA/NPs) to enhance the delivery of DTX via ligand-mediated endocytosis. The size and morphology of pD-TPGS-PLA/NPs and Gal-pD-TPGS-PLA/NPs changed obviously compared with TPGS-PLA/NPs. In vitro studies showed that TPGS-PLA/NPs, pD-TPGS-PLA/NPs and Gal-pD-TPGS-PLA/NPs had similar release profiles of DTX. Both confocal laser scanning microscopy and flow cytometric results showed that coumarin 6-loaded Gal-pD-TPGS-PLA/NPs had the highest cellular uptake efficiency in liver cancer cell line HepG2. Moreover, DTX-loaded Gal-pD-TPGS-PLA/NPs inhibited the growth of HepG2 cells more potently than TPGS-PLA/NPs, pD-TPGS-PLA/NPs, and a clinically available DTX formulation (Taxotere®). The in vivo biodistribution experiments show that the Gal-pD-TPGS-PLA/NPs are specifically targeted to the tumor. Furthermore, the in vivo anti-tumor effects study showed that injecting DTX-loaded Gal-pD-TPGS-PLA/NPs reduced the tumor size most significantly on hepatoma-bearing nude mice. These results suggest that Gal-pD-TPGS-PLA/NPs prepared in the study specifically interacted with the hepatocellular carcinoma cells through ligand–receptor recognition and they may be used as a potentially eligible drug delivery system targeting liver cancers. Statement of Significance: Polydopamine-based surface modification is a simple way to functionalize polymeric nanoparticle surfaces with ligands and/or additional polymeric layers. In this work, we developed docetaxel (DTX)-loaded formulations using polydopamine-modified NPs synthesized from D-α-tocopherol polyethylene glycol 1000 succinate-poly(lactide) (pD-TPGS-PLA/NPs). To target liver cancer cells, galactosamine was conjugated on the prepared NPs (Gal-pD-TPGS-PLA/NPs) to enhance the delivery of DTX via ligand-mediated endocytosis. Both confocal laser scanning microscopy and flow cytometric results showed that coumarin 6-loaded Gal-pD-TPGS-PLA/NPs had the highest cellular uptake efficiency for liver cancer cell line HepG2. The in vivo biodistribution experiments show that the Gal-pD-TPGS-PLA/NPs are specifically targeted to the tumor. Furthermore, the in vivo anti-tumor effects study showed that injecting DTX-loaded Gal-pD-TPGS-PLA/NPs reduced the tumor size most significantly on hepatoma-bearing nude mice. These results suggest that Gal-pD-TPGS-PLA/NPs prepared in the study specifically interacted with the hepatocellular carcinoma cells through ligand–receptor recognition and they could be used as a potentially eligible drug delivery system targeting liver cancers.